Your perfect diet match: which plans work best for your body? - Levey, Diana Kelly (Centennial Books, 2020)
"Wondering which diet plan - Keto, Paleo, Weight Watchers, Atkins, Vegetarian, Dash - to try? Get the facts on 24 popular weight loss programs, including experts' opinions and science that shows how they work"--Publisher description.